DASAR-DASAR VOICE OVER INTERNET PROTOKOL - Prawiroredjo, Kiki (Jurnal Teknik Elektro, 2002)
Voice over IP (VoIP) technology enables the real time transmission of voice signals aspacketized data over IP networks that employ the Transmission Control Protocol (TCP),Real Time Transport Protocol (RTP), User Datagram Protocol (UDP), and InternetProtocol (IP) suite. In VoIP systems, analog voice signals are digitized and transmitted as astream of packets over a digital data network. IP networks allow each packet toindependently find the most efficient path to the intended destination, thereby best using thenetwork resources at any given instant. The packets associated with a single source may thustake many different paths to the destination in traversing the network, arriving with differentend to end delays, arriving out of sequence, or possibly not arriving at all. At the destination,however, the packets are reassembled and converted back into the original voicesignal.VoIP technology insures proper reconstruction of the voice signals, compensating forechoes made audible due to the end to end delay, for jitter and for dropped packets.Variation among VoIP products include the algorithms and implementations used to supportdynamic bandwidth allocation, packet loss recovery, adaptive echo cancellation and speechprocessing to deliver voice quality as high as possible.Keywords: Voice over IP (VoIP), gateway, Digital Signal Processing (DSP)